L'histoire se répète: Why the liberalization of the EU vineyard planting rights regime may require another French Revolution. (And why the US and French Constitutions may have looked very different without weak planting rights enforcement) - Giulia Meloni; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2015)
In 2008, the EU voted to liberalize its system of planting rights which has strictly regulated vine plantings in the EU. However, after an intense lobbying campaign the liberalization of the planting right system was overturned in 2013 and new regulations created an even more restrictive system. European wine associations complained about the detrimental effects of the new regulations. There is a precedent in history. In 1726, the French political philosopher and landowner Montesquieu complained to the French King about the prohibition on planting new vines. Montesquieu was not successful in his demands to remove the planting rights. Old and recent history suggests that political forces against liberalization of planting rights are very strong. Only the French Revolution in 1789 led to a fundamental liberalization of planting rights. The "liberal period" of the 19th century was sustained by the combination of the French Revolution's liberal ideology, the thirst for wine of Napoleon's armies and diseases that wiped out most of the French vineyards. That said, in the past and the present, enforcement of planting rights is a major problem. In fact, despite the official restrictions, Montesquieu managed to plant his vines, allowing him to become a successful wine producer and merchant and to travel and to spend time thinking, discussing and ultimately writing up his ideas which influenced much of the Western world's constitutions.
Keywords: 330